Planting date and maturity group impact on soybean seed quality in the southeastern United States. (12th November 2021) - Morris, Tristan C.; Vann, Rachel A.; Collins, Guy D.; Heitman, Joshua; Kulesza, Stephanie B.
Abstract: The impacts on soybean seed quality from shifting to using earlier soybean planting dates (PDs) and earlier‐maturing varieties in the southeastern United States are not well understood. The objective of this study was to determine the impact of diverse PDs and maturity groups (MGs) on soybean protein content, oil content, seed damage, and purple seed stain. Studies were installed across seven North Carolina locations in 2019 and 2020 to determine the impact of PD (mid‐March through mid‐July) and MG (2–7) on seed quality. Protein content declined as planting was delayed for the early MGs (2–5) but was stable across PD for the later MGs (6–7). It was observed that early‐maturing varieties (MG ≤5) had a lower protein content than the later‐maturing varieties (MGs 6–7). The oil content was greater in the early MGs (MGs 2–4) compared with the later MGs (MGs 5–7), with oil content and protein content having an inverse relationship. Seed damage was greatest when planting before late April with early MGs (MGs 2–4). Less purple seed stain was found in MGs 5–7 compared with the earlier MGs across all PDs. Further research is needed to understand how to minimize seed damage and purple seed stain as producers consider shifting to an earlier production system for the associated yield benefits in North Carolina and across the southeastern United States. Core Ideas: Early‐maturing varieties had a lower protein content than later‐maturing varieties. Protein content was consistent across planting date for later‐maturing varieties. Seed damage was greatest when planting before late April with early MGs (2‐4). Purple seed stain was lower in MGs 5‐7 compared with the earlier MGs across all planting dates.